Clinical value of histologic endometrial dating for personalized frozen-thawed embryo transfer in patients with repeated implantation failure in natural cycles - Yuan Li; Xiao feng Li; Jing nan Liao; Xiang xiu Fan; Yong bin Hu; Runxin Gan; Guangxiu Lu; Ge Lin; Fei Gong (BMC, 2020)
Abstract Background Displacement of the window of implantation (WOI) has been proposed as an important factor contributing to repeated implantation failure (RIF). However, the use of histologic endometrial dating as a diagnostic tool of endometrial receptivity has been questioned. Methods This study is a prospective intervention trial that enrolled 205 infertile patients from July 2017 to December 2017. Endometrial biopsies from 50 patients with good prognoses were conducted on day 3 (n = 6), 5 (n = 6), 7 (n = 26), 9 (n = 6), or 11 (n = 6) post-ovulation (PO + 3/5/7/9/11) of the previous natural cycle before their conventional frozen-thawed embryo transfer (FET) cycle. We conducted endometrial biopsies for 155 RIF patients on day PO + 7. Results The verification of the Noyes criteria for endometrial dating was conducted at different times (PO + 3/+ 5/+ 7/+ 9/+ 11) on 41 patients with good prognoses who achieved an ongoing pregnancy in their first conventional FET cycle after endometrial biopsy. The agreement between two pathologists determining endometrial biopsy dating results in infertile patients was determined to be acceptable (weighted kappa = 0.672, P < 0.001). The rate of out-of-phase dating on day PO + 7 was significantly higher in RIF patients than in good- prognosis patients (31.6% vs. 3.8%, P = 0.003). pFET was performed in 47 RIF patients diagnosed to be out of phase, and the cumulative live-birth rate was 61.7%. Conclusions Histologic endometrial dating of RIF patients in natural cycles may be a biomarker for a receptive endometrium in diagnosing WOI displacement. Trial registration NCT03312309 Registered 17 October 2017. NCT03222830 Registered 19 July 2017,